The jon boat years : and other stories afield with fine friends, fair dogs, a shotgun, and a fly rod - Mize, Jim, 1953- (University of South Carolina Press, 2023)
"In his ability to capture the elusive essence of sport [Mize] serves as a voice for all of us. That's a rare gift and is precisely what makes The Jon Boat Years a treasure that should be read and enjoyed not just now but for generations to come"--